Anti-aging Effect and Mechanism of Ethanol Extract of Clinacanthus nutans on Caenorhabditis elegans - Yanping ZHUANG; Fan YANG; Man XIAO; Xiaoyu TIAN; Yi CHEN; Ziyu LONG; Bocen CHEN; Yali NI; Aimin GONG; Yiqiang XIE (Shipin gongye ke-ji, 2023)
Objective: To assess the anti-aging effect and mechanism underlying the effects of ethanol extract from Clinacanthus nutans (CNEE) using Caenorhabditis elegans as the model organism. Methods: The anti-aging effects of ethanol extract from Clinacanthus nutans on nematodes were detected by experiments to assay longevity, oviposition, and exercise. The antioxidant capacity of the ethanolic extracts from Clinacanthus nutans and their mechanisms of action in delaying aging were investigated by assessing the acute oxidative stress, determining the antioxidant enzyme activity, and determining the reactive oxygen species (ROS) levels along with real-time fluorescence quantitative PCR experiments. Results: The ethanol extract from Clinacanthus nutans at 100 μg/mL could prolong the life span of N2 wild type nematode (P<0.001), promote the ability to exercise (P<0.001), and exerted no toxic effects on oviposition (P>0.05). The extract also increased nematode longevity (P<0.05) and catalase activity (P<0.01) under acute oxidative stress conditions, and effectively reduced the accumulation of ROS in vivo (P<0.05) along with upregulating the levels of daf-16 (P<0.01) and downstream ctl-1 (P<0.001) gene expressions. However, in daf-16 mutant nematodes, effects on life extension under normal conditions or acute oxidative stress were not observed, nor was there an increase in catalase activity, a decrease in ROS levels, or an increase in daf-16 and ctl-1 levels (P>0.05). Conclusion: The ethanol extract from Clinacanthus nutans enhanced the ability of nematodes to resist aging and the underlying mechanism of action may be related to the regulation of oxidative stress by daf-16.